Association of serum ferritin and glycated haemoglobin in patients of type 2 diabetes mellitus and its correlation with components of metabolic syndrome - Saluja, Manoj; Suman, Chetan Prakash; Chittora, Saurabh; Meena, Dileep (International Journal of Research in Medical Sciences, 2022)
Background: Ferritin is a universal intracellular protein that stores iron and releases it in a controlled fashion, and reflects iron stores of the body. Recent studies indicate that increased body iron stores are associated with development of type 2 diabetes mellitus (DM) hence affecting the level of glycated haemoglobin. The aim and objectives of this study were to determine the relationship between serum ferritin and glycated haemoglobin in type 2 diabetes patients and to find out correlation between serum ferritin level and components of metabolic syndrome. Methods: This study included 100 cases of type 2 DM compared with age and sex-matched 100 non-diabetic controls. Serum ferritin, fasting blood sugar, lipid parameters and waist circumference were estimated, and glycated haemoglobin was calculated by HPLC method. Results: The mean serum ferritin in cases was 178.59±84.17 µg/l and in controls was 107.17±13.83 µg/l (p=0.0001). The mean age was 53.32±10.14 years in cases and 51.8±10.54 years in controls. Mean HbA1C level in cases was higher (8.40±1.22) as compared to controls (5.4±0.34) and it was statistically significant (p<0.0001). There was a positive linear correlation between HbA1C level and serum ferritin irrespective to gender in case group (r=0.342) and it was statistically significant (p<0.0001). Serum ferritin was significantly higher in hypertensive type 2 DM patients than hypertensive non-diabetic patients (p<0.0239). Conclusions: The findings of this study suggest that increased level of serum ferritin is positively related to glycaemic control.